Studies of disturbances in the polar ionosphere and thermosphere with the EISCAT radar system and whole atmosphere GCM - Fujiwara, Hitoshi; Nozawa, Satonori; Ogawa, Yasunobu; Miyoshi, Yasunobu; Jin, Hidekatsu; Shinagawa, Hiroyuki; Kataoka, Ryuho; Liu, Huixin (2017)
18th EISCAT symposium Session E7: Space weather and modelling May 26 (Fri), NIPR Auditorium conference object